Biomental child development : perspectives on psychology and parenting - Ninivaggi, Frank John (Rowman & Littlefield Publishers, 2012)
Biomental Child Development: Perspectives on Psychology and Parenting provides the reader with a basic understanding of child, adolescent, and adult psychology, and applies it to the growth of the integrated body and mind of children, from infancy through childhood. It offers caregivers a roadmap and a philosophy for positive parenting.